Occupations and the new HEIC job market in the context of the Covid-19 pandemic - Gimnez, Denis Maracci; Cajueiro, Juliana Pinto de Moura (Cadernos do Desenvolvimento, 2023)
This study investigates the new job market in the Health Economic-Industrial Complex (HEIC 4.0) and its influence on occupations. It also discusses the structural characteristics of the HEIC dynamics and the Unified Health System (SUS) sustainability in the pandemic context. Divided into three sections, this article highlights that health occupations are simultaneously impacted by a general social and job market degradation. There are also restrictions imposed on the HEIC modernization process, which is the cornerstone of SUS. In the second section, it focuses on the health care occupation conditions and fragilities, heightened during the pandemic. Finally, it establishes relations between structural movements in the job market and the needs for modernizing HEIC and its impact on the health care working conditions. The HEIC conditions and fragilities seen during the pandemic reflect general issues in Brazil’s development pattern.